In Vitro Biocompatibility Assessment of Entomopathogenic Fungi and Plant Leaf Extracts - Almas, Muniza; Mirza, Safdar Ali (AGRIVITA Journal of Agricultural Science, 2025)
Entomopathogenic fungi are potential candidates for ecofriendly pest-management. These fungi with botanical extracts can improve control over insect pests of economical crops. This study assessed the biocompatibility between four fungi (Aspergillus flavus, Aspergillus oryzae, Metarhizium flavoviride, and Trichoderma hamatum) and four aqueous plant leaf extracts (Azadirachta indica, Eucalyptus camaldulensis, Melia azedarach, and Ocimum sanctum). The fungal strain pure cultures were procured from the Fungal Culture Bank, University of the Punjab, Lahore. Leaf extracts were employed at 0.25% to 1% concentrations, whereas fungal inocula were maintained at 1 × 108 conidia/ml. Fungal dry mycelial weight (DMW), colonial growth (CG), and conidial density (CD) were recorded on PDB and PDA media with leaf extracts. Compatibility was calculated based on DMW, CG, and CD results. Aspergillus flavus was highly compatible with 0.25% to 1% A. indica leaf extract. Aspergillus oryzae was compatible with 0.5% to 1% E. Camaldulensis and 0.25% M. azedarach leaf extracts. Metarhizium flavoviride was compatible with 0.5% to 1% E. Camaldulensis and 1% M. azedarach leaf extracts. Trichoderma hamatum shared high compatibility with most concentrations of plant extracts and emerged as the most promising strain. These findings promote fungi-plant extract combination as an ecofriendly pest-management alternative.